Screening of Malaysian rice accessions and marker-assisted selection of a cross between MR263 × swarna-sub1 varieties for submergence tolerance - Mojulat, Welland Cosmas (2015)
Submergence is considered as one of the principal cause of crop failure worldwide causing major constraint in world rice production as well as in Malaysia. Several rice fields at Kelantan, Terengganu, and Pahang in Malaysia have been affected by flash flood and resulted in rice yield loss. Sub1, a gene which is responsible for submergence tolerance and has been utilized to developed several rice submergence tolerance varieties namely, Swarna-Sub1, BR11-Sub1, IR64-Sub1 and Samba Mahsuri-Sub1. The discovery of Sub1 gene is a breakthrough which can be introgressed into local popular variety to produce high yielding variety with submergence tolerance in Malaysia. Thus, improving crops capacity to withstand such stress is therefore a fundamental importance. In this study, 12 accessions were identified with high survival against submergence, namely, Mayang, Pagalan, Siong pelanduk 6, Labou, Bangkok (H), Babang, Renjan bembang, Bedor, Semilai, Tatalunalis, Langsat and Merjat. This outcome shows that Malaysia has its own submergence tolerance genetic source yet extensive research in the future is essential to test stability of these accessions to be used as alternative source for submergence tolerance. The study also shown that the Malaysian commercial rice varieties namely, MR219, MR220 and MR263 were severe susceptible to submergence. These results provide the real purpose to develop submergence tolerance variety for stability in crop production with an increased economic value in nowadays extreme changing environments. First step towards the development of submergence tolerance variety starts with the breeding program by crossing MR263 and Swarna-Sub1. Marker-assisted selection (MAS) was carried out through the utilization of simple sequence repeats (SSR) considering it is rapid and reliable for pre-selection tools. F1 generations were confirmed by polymorphic linked marker, RM8300 and RM219. Out of 180 SSR markers, 30 markers were found polymorphic between two parents. Association of molecular markers and submergence tolerance were determined using Chi-square revealed that the MR263 × Swarna-Sub1 F2 lines carried Sub1 tolerance gene associated with SSR markers, RM413, RM1233, RM8225, RM5961, RM219 and RM8300. These markers showed a good fit to the expected marker segregation ratio (1:2:1) in a Mendelian single gene model (DF=1.0, p≤0.05). Eleven homozygous lines with linked Sub1 gene marker were selected for future development of submergence tolerant varieties. We thus selected a subset of 11 fitness compromised tolerance lines out of 256 lines linked Sub1 gene from the F2 generation and screened them for submergence tolerance for phenotypic performance. The selected 11 lines from previous molecular experiment were verified by evaluating its submergence survival and yielding performance for selection of the best lines. The 11 lines were confirmed phenotypically submergence tolerance. Through yield performance evaluation, all accessions were grouped into three clusters. Finally, from this study the best four accessions, namely L05, L08, L09 and L11 were identified for the further development of high yielding submergence tolerant rice variety.